2007
DOI: 10.1159/000107940
|View full text |Cite
|
Sign up to set email alerts
|

Monovoxel <sup>1</sup>H Magnetic Resonance Spectroscopy in the Progression of Gliomas

Abstract: Aim: Can monovoxel magnetic resonance spectroscopy (MRS) reliably follow tumour progression in low-grade glioma? Materials and Methods: 21 patients with low-grade glioma underwent at least 3 MRS. Results: For progression from a grade II to grade III tumour, a sensitivity of 57.1% and specificity of 60% were observed, with a positive predictive value (PPV) of 48.8% and a negative predictive value (NPV) of 54.5%. For progression under treatment, we obtained a sensitivity of 57.1% by N-acetylaspartate (NAA)/choli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 122 publications
(150 reference statements)
0
11
0
Order By: Relevance
“…11). 17,18 A multivoxel spectroscopic approach may help in identifying the most aggressive part of a large lesion.…”
Section: Epilepsymentioning
confidence: 99%
“…11). 17,18 A multivoxel spectroscopic approach may help in identifying the most aggressive part of a large lesion.…”
Section: Epilepsymentioning
confidence: 99%
“…8 Previous studies have demonstrated the utility of MR spectroscopy in predicting or prognosticating MT and survival of those with LGGs. [9][10][11][12][13][14][15] To the best of our knowledge, the role of MR spectroscopy in diagnosing MT among LGGs with increased contrast enhancement has not been investigated. In the present study, using histopathology as the criterion standard, we aimed to determine the value of MR spectroscopy to diagnose MT in a group of patients who had a prior diagnosis of LGG and an increase in contrast enhancement on follow-up MR imaging.…”
mentioning
confidence: 99%
“…For example, NAA/Cho and Cho/Cr ratios are reported in brain tumor studies (31)(32)(33)(34). However, due to the lack of neurons in the U87MG tumors, NAA (Nacetyl aspartate) was not present, precluding use of a NAA/Cho ratio.…”
Section: Discussionmentioning
confidence: 99%